Legal Protection for Victims of Crimes of Abuse That Result in Serious Injuries: A Human Rights Perspective - Ismail, Naufal; Gagarin Akbar, M. Gary; Abas, Muhamad (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
Human Rights (HAM) are inherent rights that every person possesses from birth and must be respected by all individuals. In the case of decision number 467/Pid.B/2022/PN.Dpk., the victim of the abuse did not receive their due rights for the suffering and losses endured. This study employs a normative legal research method with a juridical normative approach to analyze human rights theories and relevant legislation concerning legal protection for victims of criminal acts in Indonesia. The findings reveal that such acts of abuse violate human rights values ​​enshrined in both national and international regulations. The state plays a crucial role in restoring the human rights of victims to ensure legal protection and justice. Legal protection should include judges' understanding of victims' rights, including the application for restitution and compensation, as well as the merging of criminal and civil cases.